Effectiveness of triamcinolone Acetonide Injection for the treatment of Non-infectious Intermediate and Posterior Uveitis - Ahmed, Iftikhar; Alvi, Rashid Hassan; Maaz Allah; Sarah Saleem; Muhammad Nizamuddin (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To assess the efficacy of posterior sub-tenon injection (PSTI) of Triamcinolone Acetonide (TA) in patients with Uveitis. METHODS: This prospective study was conducted from July 2022 to May 2023. A total of 160 eyes were comprehensively examined at the Kulsoom Bai Valika Social Security Site Hospital and Sindh Government Qatar Hospital. Purposive sampling was employed for participant selection, focusing on the eye with poor vision in patients with Uveitis in both eyes. The sample was stratified into non-infectious posterior Uveitis and non-infectious intermediate Uveitis, maintaining a 1:1 ratio. Statistical analysis was performed using SPSS (version 25.0). RESULTS: The median duration of Uveitis was 20.5 weeks (interquartile range, IQR: 17-25). The median best-corrected visual acuity before treatment was 0.5 (IQR: 0.4-0.7). After one week, it improved to 0.2 (IQR: 0.1-0.3), and after three months, it further increased to 0.12 (IQR: 0.1-0.18), showing a statistically significant difference (p-value < 0.01) between baseline and one week after treatment. The difference between one week and after 12 weeks remained consistent. Two-way analysis also revealed a significant difference (p-value < 0.01). CONCLUSION: Posterior sub-tenon injection of triamcinolone acetonide is effective and safe for treating non-infectious Uveitis. The intraocular pressure did not show an increase following the injection, and visual acuity significantly improved after PSTI.